Goat Farming System in Kolaka District, Southeast Sulawesi (Pascasarjana Universitas Sulawesi Tenggara, 2022)
This study aims to identify the goat farming system in Kolaka Regency by collecting research data from primary and secondary data. The determination of the research location was carried out by purposive sampling, namely choosing the research location intentionally based on the consideration that the research location had the largest population of goats in Kolaka Regency in 2021. The selected subdistricts were Watubangga, Toari, and Tanggetada Districts. Each sub-district is represented by 3 villages and each village consists of 10 farmers as research respondents. The results of research on goat breeding systems in Kolaka Regency are generally carried out intensively (36.7%), semi-intensively (32.2%), and extensively (31.1%). The characteristics of the breeder include the age of the breeder, a person's education level, feeding, as well as housing.